2016
DOI: 10.4038/cmj.v61i1.8260
|View full text |Cite
|
Sign up to set email alerts
|

Predicting acute liver failure in dengue infection

Abstract: In a retrospective study involving 240 patients with dengue infection, we attempted to identify early predictors of acute liver failure (ALF). Sixteen out of 41 patients with serum AST more than 1000 IU/ml developed ALF compared to none with serum AST less than 1000 IU/ml. Among patients with serum AST more than 1000 IU/ml, presence of two of the three following phenomena, within the first 5 days of illness: elevated serum bilirubin, elevated alkaline phosphatise or persistent nausea and vomiting, predicted de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
1
6
0
2
Order By: Relevance
“…Regarding the liver biochemistry, the mean levels of bilirubin, transaminases, and alkaline phosphatase were higher in the ALF group than in the non-ALF group, which was in accordance with findings from previous studies[ 7 , 12 , 14 , 17 ]. The degree of transaminase elevation in our study was relatively higher than that in other studies[ 11 , 18 ] (15-20 times the normal level); however, we did not find an association between the presence of extremely high transaminase levels or increasing levels of other biochemistry outcomes and the development of ALF from DISH.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the liver biochemistry, the mean levels of bilirubin, transaminases, and alkaline phosphatase were higher in the ALF group than in the non-ALF group, which was in accordance with findings from previous studies[ 7 , 12 , 14 , 17 ]. The degree of transaminase elevation in our study was relatively higher than that in other studies[ 11 , 18 ] (15-20 times the normal level); however, we did not find an association between the presence of extremely high transaminase levels or increasing levels of other biochemistry outcomes and the development of ALF from DISH.…”
Section: Discussionsupporting
confidence: 92%
“…El uso actual de sistemas no biológicos como el de recirculación molecular adsorbente (MARS, por sus siglas en ingles), se ha practicado con seguridad en FHA de diferentes etiologías, mostrando beneficios sobre la ictericia, la inestabilidad hemodinámica, la hipertensión portal y endocraneana, y la encefalopatía hepática con reportes favorables en la FHA por dengue (18). Finalmente, el éxito con resolución del shock por dengue y la FHA gracias al trasplante hepático ha sido documentado en pocos casos por la baja disponibilidad en países donde el DENV es prevalente, pero pudiera ser una alternativa en centros que cuenten con programa de trasplante (19)(20).…”
Section: Discussionunclassified
“…with sALI or ALF) seems to be more prevalent in children [26] than in adults, it occurred in two patients in our series. In a retrospective study from Sri-Lanka, Kumarasena et al found a 39% risk of ALF in adults with SD and sAT activity above 1,000 UI/L (approximately 30 times the ULN) [27]. Consequently, an empiric strategy of early IV-NAC infusion, the recognised antidote against APAP hepatotoxicity [28], could be a therapeutic option for adults affected by dengue with such an increased sAT activity (even with no obvious features of APAP hepatotoxicity), especially when associated with at least two of the following three features: persistent nausea and vomiting, increased serum alkaline phosphatase, and serum bilirubin levels (27).…”
Section: Discussionmentioning
confidence: 99%